2014
DOI: 10.1002/cncr.29073
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of thyroid malignant pathologic findings identified during 3 rounds of screening (1997‐2008) of a cohort of children and adolescents from Belarus exposed to radioiodines after the Chernobyl accident

Abstract: Background Recent studies of children and adolescents exposed to radioactive iodine-131 (I-131) after the 1986 Chernobyl nuclear accident in Ukraine showed significant dose-related increase in the risk of thyroid cancer, but the association of radiation doses with tumor histological and morphological features is not clear. Methods A cohort of 11,664 individuals in Belarus ≤18 years at the time of the accident underwent three cycles of thyroid screening in 1997-2008. I-131 thyroid doses were estimated from in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
46
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 33 publications
(44 reference statements)
2
46
0
1
Order By: Relevance
“…Here, outcomes and histology were directly contrast in 92 RE+ DTC patients and 165 RE-DTC patients, all treated and followed at the same institution over the same time period for a median length of 27 years. In light of initial historic reports suggesting thyroid cancer after RE was more aggressive and, more recently, equivalent to thyroid cancer in the absence of RE, it was a surprise to observe in this cohort that OS for RE+ DTC patients is significantly better than that for RE-DTC patients (18). There was no difference between the groups for either DTC-specific mortality or risk of recurrence, similar to findings reported for the Chernobyl cohort (2,3).…”
Section: Discussionsupporting
confidence: 74%
“…Here, outcomes and histology were directly contrast in 92 RE+ DTC patients and 165 RE-DTC patients, all treated and followed at the same institution over the same time period for a median length of 27 years. In light of initial historic reports suggesting thyroid cancer after RE was more aggressive and, more recently, equivalent to thyroid cancer in the absence of RE, it was a surprise to observe in this cohort that OS for RE+ DTC patients is significantly better than that for RE-DTC patients (18). There was no difference between the groups for either DTC-specific mortality or risk of recurrence, similar to findings reported for the Chernobyl cohort (2,3).…”
Section: Discussionsupporting
confidence: 74%
“…Of these, eight underwent thyroid surgery and pathology revealed that one had a benign thyroid nodule while the remaining seven subjects had thyroid cancer. None of the thyroid cancers detected in our survey were the solid variant of papillary thyroid carcinomas that were predominantly observed in Chernobyl [13]. Our challenging commencement of TUE in Fukushima also raises another clinical problem on an appropriate treatment for early detection of childhood thyroid cancer, which should be separately discussed [14,15].…”
Section: Discussionmentioning
confidence: 83%
“…Morphologically, TC in patients from contaminated territories were more aggressive than usual [11][12][13][14]. Correlations between radiation doses to the thyroid, tumor invasiveness and "aggressive solid-follicular" pattern were reported [9,10]. However, the time factor was not discussed in Bogdanova et al [9]: the cases with higher doses were probably diagnosed averagely earlier, when the pool of neglected cancers was still untapped.…”
Section: Introductionmentioning
confidence: 98%
“…Accordingly, there was a pool of undiagnosed TC prior to the accident. The percentage of more advanced cancers was negatively associated with the time between the accident and surgery [8][9][10] probably due to the gradual exhaustion by the screening of the pool of advanced cancers. Morphologically, TC in patients from contaminated territories were more aggressive than usual [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%